Proceso de Atención de Enfermería en paciente de 32 años de edad con peritonitis. - Oleas Cevallos, Ana Gabriela (2020)
Peritonitis is a general or localized inflammatory process of the peritoneal membrane caused by chemical irritation, bacterial invasion, local necrosis, or direct peritoneum contusion. Intra-abdominal sepsis includes severe peritoneal inflammation caused by pathogenic microorganisms and their products. This process can be localized (abscess) or of a diffuse nature. Symptoms may be light in immunosuppressed patients, corticosteroid users, diabetics who encounter advanced neuropathy. It is a common cause of morbidity in the surgical patient and complication of many intraabdominal interventions. This study writes a patient who goes to the emergency area for presenting abdominal pain in the epigastric region, with irradiation to left ilia pit of approximately 8 hours of evolution, accompanied by nausea and vomiting, was admitted immediately, where he was clinical examination and was carried out complementary studies that helped contribute to the definitive diagnosis, he was applied antipyretic medication and pre-antibiotic prophylaxis surgical , where no complications were determined. The patient moves into the post-surgery recovery area, with restriction of oral food intake, wound healings and daily wanderings are performed that contribute to physical mobility by nurses is also given, saline solution 0.9% 1000 cc iv 25 drops per min, antibiotic ampicillin therapy +IBL 1500 mg immediately and a gastric protector with omeprazole 40 mg Iv daily, antibiotic ampicillin therapy +IBL 1500 mg immediately and a gastric protector with omeprazole 40 mg Iv daily , after highlighting the favorable evolution is discharged with reference to its corresponding health unit.